2020
DOI: 10.2298/jsc191217018j
|View full text |Cite
|
Sign up to set email alerts
|

The phenolic profile of strawberry tree (Arbutus unedo L.) honey

Abstract: Despite of the many beneficial health effects of strawberry tree (Arbutus unedo L.) honey, due to its strong antioxidant activity derived mostly from polyphenols, a detailed phenolic profile has not been previously studied. The aims of this study were to identify the phenolic compounds, determine the total phenolic content (TPC) and evaluate the radical scavenging activity (RSA) of strawberry tree honey from south Croatia. Fifty-two polyphenolics (twenty-seven phenolic acids and twenty-five flavonoids) were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…A strong positive relationship was found between total phenolic content (TPC) and 1,1-diphenyl-2-picrylhydrazyl (DPPH), TPC and concentration of homogentisic acid homogentisic acid (HGA), and between DPPH and HGA in strawberry tree honey from Croatia [ 66 , 67 ]. A further study on Croatian strawberry tree honey revealed fifty-two phenolic compounds (twenty-seven phenolic acids and twenty-five flavonoids).…”
Section: Antioxidant Activity and Other Health Benefitsmentioning
confidence: 99%
“…A strong positive relationship was found between total phenolic content (TPC) and 1,1-diphenyl-2-picrylhydrazyl (DPPH), TPC and concentration of homogentisic acid homogentisic acid (HGA), and between DPPH and HGA in strawberry tree honey from Croatia [ 66 , 67 ]. A further study on Croatian strawberry tree honey revealed fifty-two phenolic compounds (twenty-seven phenolic acids and twenty-five flavonoids).…”
Section: Antioxidant Activity and Other Health Benefitsmentioning
confidence: 99%
“…The STH sample was collected in Vrgorac (43.20 °N 17.37 °E), Croatia in 2016. Its botanical origin was confirmed earlier by melissopalynological and sensory analyses ( 9 ) and identification of its specific chemical marker HGA. The mass fraction of HGA in the honey sample, also determined earlier by gas chromatography-mass spectrometry (GC-MS) ( 10 ), was 306.8 mg/kg.…”
Section: Methodsmentioning
confidence: 63%
“…Several studies have shown that STH has a very high content of phenolic compounds and strong antioxidant capacity. Compared to other types, this unifloral honey has greater ability to defend the body from harmful reactive oxygen species (ROS) ( 4 , 5 ). It also exerts antibacterial and anti-inflammatory activity with high anti-mutagenic and anti-proliferative properties important for tumour prevention and treatment ( 6 , 7 ).…”
mentioning
confidence: 99%
“…As a bitter substance in bamboo shoots, homogentisic acid was first reported in Japan, and Chizu Hasegawa suggested that homogentisic acid is responsible for a special taste of bamboo shoot, called egumi-taste, described as bitter and pungent [28,64]. Homogentisic acid has also been found to be the main bitter substance of bitter strawberry honey produced in Italy [65,66]. Homogentisic acid, one of the differentially downregulated metabolites in this study, together with the typical bitter phenolic acids mentioned above, could be mapped to the tyrosine metabolism pathway.…”
Section: Molecular Basis Of Reducing the Bitter Taste Of P Amarus Bam...mentioning
confidence: 99%